Immune Response to Lactobacillus plantarum Expressing Borrelia burgdorferi OspA Is Modulated by the Lipid Modification of the Antigen - del Rio, Beatriz; Seegers, Jos F. M. L.; Gomes-Solecki, Maria (PLOS ONE, 2010)
Background Over the past decade there has been increasing interest in the use of lactic acid bacteria as mucosal delivery vehicles for vaccine antigens, microbicides and therapeutics. We investigated the mechanism by which a mucosal vaccine based in recombinant lactic acid bacteria breaks the immunological tolerance of the gut in order to elicit a protective immune response. Methodology/Principal Findings We analyzed how the lipid modification of OspA affects the localization of the antigen in our delivery vehicle using a number of biochemistry techniques. Furthermore, we examined how OspA-expressing L. plantarum breaks the oral tolerance of the gut by stimulating human intestinal epithelial cells, peripheral blood mononuclear cells and monocyte derived dendritic cells and measuring cytokine production. We show that the leader peptide of OspA targets the protein to the cell envelope of L. plantarum, and it is responsible for protein export across the membrane. Mutation of the lipidation site in OspA redirects protein localization within the cell envelope. Further, we show that lipidated-OspA-expressing L. plantarum does not induce secretion of the pro-inflammatory cytokine IL-8 by intestinal epithelial cells. In addition, it breaks oral tolerance of the gut via Th1/Th2 cell mediated immunity, as shown by the production of pro- and anti-inflammatory cytokines by human dendritic cells, and by the production of IgG2a and IgG1 antibodies, respectively. Conclusions/Significance Lipid modification of OspA expressed in L. plantarum modulates the immune response to this antigen through a Th1/Th2 immune response.